Deferiprone ameliorates cisplatin induced peripheral neurotoxicity via ferritinophagy adjustment - Hanan Seddiek; Mira Hanna; Amany Elsayed Mohamed Hamoud; Marawan Abd Elbaset; Ahmed M. A. Akabawy; Mohamed Zakaria Kotb; Mohamed Mansour Khalifa (Scientific Reports)
Abstract Cisplatin-induced neurotoxicity is one of the limiting factors to its use especially in tumors that demand high drug dosage. One of the Cisplatin pathways is ferritinophagy which may end up in ferroptosis. So, we aimed to use iron chelator as a new strategy based on an anti-ferroptotic mechanism and to evaluate its neuroprotective effect against polyneuropathy in Cisplatin-treated rats. Twenty-four male Wistar albino rats were arranged into four groups: (I) Control group, rats were given vehicle; (II) Def group, rats received deferiprone (200 mg/kg orally once daily for 10 days); (III) Cis group, rats were injected by Cis 2 mg/Kg once daily for 3 consecutive days i.p.; and (IV) Cis + Def group, rats received deferiprone (200 mg/kg orally once daily for 10 days, rats were injected with Cis in the 4th, 5th, and 6th days). Cis increased and upregulated ferritinophagy inducers significantly including MDA, NCOA4, and IREB1 as compared to the control group. On the other hand, GSH, GPX4, SLCA11 and FTH1 were decreased and down regulated significantly compared to the control group. In addition to significant deterioration in the histopathological and immunological nerve tissue assessment using silver stain and PNCA. Embracing the cisplatin dosage with deferiprone reversed cisplatin-induced neuropathy, in which the physiological function significantly improved along with the immune and histopathology of nerve tissue. This was accompanied by down regulation of ferritinophagy inducers and enhancing ferritinophagy inhibitors. The current results concluded that rapping cisplatin with deferiprone can mitigate neurotoxicity induced by cisplatin in experimental animals through ferritinophagy pathway adjustment.